Analisis Faktor-Faktor Yang Mempengaruhi Keputusan Debitur Dalam Memilih Produk KPR Bersubsidi Pada Perusahaan PT. Madani Sejahtera Investasi - Hadrah, Ainin; Nurhayati, Siti (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
The limited access of low-to-middle-income communities to affordable and decent housing persists despite the increasing demand for subsidized mortgage (KPR Bersubsidi) homes at PT. Madani Sejahtera Investasi. This study aims to determine the influence of Service and Administration, Promotion, and Building Quality factors on debtors' decisions in choosing subsidized mortgage products at PT. Madani Sejahtera Investasi. This research employs a quantitative approach, with data collection conducted through questionnaires targeting a population of debtors who have opted for subsidized mortgage products at PT. Madani Sejahtera Investasi. The sampling technique used is Non-Probability Sampling. Data analysis is performed using multiple linear regression analysis with SPSS software. The findings indicate that the Service and Administration variable has a positive and significant influence on debtors' decisions in choosing subsidized mortgage products at PT. Madani Sejahtera Investasi. The Promotion variable has a negative but not significant influence on debtors' decisions, while the Building Quality variable has a positive and significant influence on debtors' decisions. Based on these findings, it is recommended that PT. Madani Sejahtera Investasi enhance its evaluation of effective promotional outreach to ensure that the public is aware of the availability of subsidized mortgage products offered by the company.